(3GdCOhjI GdbdHjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3eMeO Hf YHO Gddg GdhGSWi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe Ef Gddg SHMGfg Ndb GdJLhja GdCjSQ ef JLhja GdbdH NRGfI ddQhM heYhfG dJhdOg , hNdb GdQhM eWjHI ddbhi GdfaSGfjI s
(3BNQgG (B:s
(3agPG eG GNfUQfG ef GdcdGe hGdCLOhjI GdbHjI Ydi CbUi eG jecf efi GdGNJUGQ ,hbO MGf dfG Cf fJe GdebGdI MGeOjf GdhGgH Gdbhi JJejegG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B66s
(3eDdaGJ GHf SjfG dLhQL bfhGJi Qbe (B111s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B6 s
Keywords: (3GdWHs